Counter-institutionalizing First Nation–Crown relations in British Columbia. (November 2020) - Persaud, Anthony W.; Satterfield, Terre; Macdonald, Eliana
In Canada, the advance of industrial resource extraction has been moderated by a series of key legal decisions that have found that development activities within the traditional territories of Indigenous Nations may infringe on Aboriginal and treaty rights, requiring a duty to consult and potentially accommodate those affected. In British Columbia this duty is primarily satisfied through the Crown referrals process, whereby affected First Nation groups are notified by the Crown regarding potential rights-affecting decisions and are given an opportunity to formulate a response. This form of institutionalized engagement presents an ongoing challenge for First Nation groups who struggle to manage the influx of Crown referrals, as well as a dilemma for those who question its fairness and inherent colonial structure. For others, it is seen as an opportunity to leverage the duty to consult and accommodate in order to strengthen territorial self-governance. In this paper we introduce the idea of counter-institutionalizing and explore the conditions under which the Crown referrals process is being redrawn to better address, and not, the ability of First Nation groups to improve territorial self-governance and the trade-offs involved.